1993
DOI: 10.1021/j100124a044
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved resonance Raman and surface-enhanced resonance Raman scattering study on monocation radical formation processes of heptylviologen at silver electrode surfaces

Abstract: Time-resolved resonance Raman and surface-enhanced resonance Raman scattering (RRS and SERRS) spectra were measured for the monocation radical of heptylviologen (HV'+) formed on a silver electrode surface as a function of time ( t ) after switching the electrode potential from -0.2 V (vs Ag/AgCl) to -0.65 V (the monocation radical formation potential). The intensity of the R R S band at 1530 cm-I due to HV'+ increases as a linear function of t 3 / 2 in the first step (0 to ca. 4 ms) and as a linear function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Coupling surface interrogation SECM (SI-SECM) to Raman spectroscopy enables us to comprehensively study the charge transfer mechanism in RAC monolayer films (Figure b). Viologen derivatives have multiple Raman-active peaks that allow structural changes to be observed during the reduction to the radical cation and neutral form. ,, A strong resonance Raman signal from V + · arising from an absorption region (540 nm) near the excitation wavelength (532 nm), allows monitoring of the signal on non-noble electrode surfaces, circumventing the need for surface-enhancement . Raman spectroscopy has previously been coupled to shear force SECM, but this is the first time that SECM measurements have been used in situ with Raman spectroscopy with the intention of monitoring transient processes.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling surface interrogation SECM (SI-SECM) to Raman spectroscopy enables us to comprehensively study the charge transfer mechanism in RAC monolayer films (Figure b). Viologen derivatives have multiple Raman-active peaks that allow structural changes to be observed during the reduction to the radical cation and neutral form. ,, A strong resonance Raman signal from V + · arising from an absorption region (540 nm) near the excitation wavelength (532 nm), allows monitoring of the signal on non-noble electrode surfaces, circumventing the need for surface-enhancement . Raman spectroscopy has previously been coupled to shear force SECM, but this is the first time that SECM measurements have been used in situ with Raman spectroscopy with the intention of monitoring transient processes.…”
Section: Introductionmentioning
confidence: 99%
“…20 Upon the synchronization of the laser pulses with triggering of a gatable photodiode array, the time resolution was limited by the laser pulse width. While this approach was restricted to m onitoring of photoinduced reactions on the electrode surface, Misono et al 17 studied potential jump-induced reactions by employing a pulsed laser to probe TR SE RR spectra with a time-resolution determined by the pulse width of the laser.…”
Section: Introductionmentioning
confidence: 99%
“…15,33 Radicals of bisviologens linked by flexible organic bridges form dimers of remarkable stability by intramolecular process. [30][31][32] Cyclodextrins (CDs) are cyclic oligosaccharides that possess hydrophobic cavities capable of forming inclusion complexes with a variety of organic molecules in aqueous solution. [34][35][36] Several investigators have reported the results of studies on the interaction of viologens with CDs and the effect of CDs on the dimerization of viologen radicals.…”
Section: Introductionmentioning
confidence: 99%
“…V •+ is known to dimerize in solution. , The dimer formation affects the electrochromic properties of viologens 6,7,28 and further reactions where V •+ participates. ,, The dimers have been characterized by UV−vis, ,,,, ,, IR, Raman, , and ESR 13 spectroscopies. The reported monomer−dimer equilibrium constant ( K D ) for dimethyl viologen radical cation (C 1 C 1 V •+ ) in aqueous solutions around 25 °C is in the range of 380−840 M -1 . ,,,, The ambiguity of the UV−vis spectroscopic parameters of the viologen dimer might be responsible for the wide range of the reported K D values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation